Case report: the addition of olfaction to virtual reality enhanced exposure therapy for PTSD - Freedman, Sara A.; Dayan, Ehud; Senitsky, Michal; Bellin, Elisheva; Attias, Yossi; Richman, Tzvi; Eitan, Renana; Tatsa-Laur, Lucian (Frontiers in Virtual Reality, 2024)
Post-traumatic stress disorder (PTSD) occurs in approximately 20% of individuals following exposure to a potentially traumatic event. Re-experiencing in the form of intrusive memories is a hallmark feature, and often includes sensory elements, including odor. A small body of studies have examined the relationship between PTSD and odor evoked memories. Patients avoid smells that remind them of their traumatic event, and odors are known triggers for intrusive memories and distress. PTSD is associated with higher ratings of odor intensity and unpleasantness however accuracy of odor detection is often impaired.It has been suggested that adding trauma-related odors will enhance treatment, however little data exists. This case study illustrates the addition of trauma specific olfaction in Virtual Reality (VR) enhanced exposure therapy for combat related PTSD. Treatment was successful, the patient no longer met criteria for PTSD at the end of treatment, and self-report symptoms scores indicated clinically significant reductions. The patient indicated at the end of treatment that he would not have been helped had the therapy not used VR, and the addition of odors helped him process the traumatic memories. Future research should assess the addition of olfaction in a systematic way, in order to assess its specific impact in the effectiveness of PTSD treatment.